Mesenchymal stem cell-derived exosomes from different sources selectively promote neuritic outgrowth. (21st April 2016) - Lopez-Verrilli, M.A.; Caviedes, A.; Cabrera, A.; Sandoval, S.; Wyneken, U.; Khoury, M.
Highlights: Menstrual stem cell-derived exosomes selectively promote neurite growth. Mesenchymal stem cell exosomes of different origins were compared. Our results are relevant for future therapeutic applications in neurological diseases. Abstract: Mesenchymal stem cells (MSCs) obtained from bone marrow (BM) have been shown to promote neuronal growth and survival. However, the comparative effects of MSCs of different sources, including menstrual MSCs (MenSCs), BM, umbilical cord and chorion stem cells on neurite outgrowth have not yet been explored. Moreover, the modulatory effects of MSCs may be mediated by paracrine mechanisms, i.e. by molecules contained in the MSC secretome that includes soluble factors and extracellular vesicles such as microvesicles and/or exosomes. The biogenesis of microvesicles, characterized by a vesicle diameter of 50 to 1000 nm, involves membrane shedding while exosomes, of 30 to 100 nm in diameter, originate in the multivesicular bodies within cells. Both vesicle types, which can be harvested from the conditioned media of cell cultures by differential centrifugation steps, regulate the function of target cells due to their molecular content of microRNA, mRNA, proteins and lipids. Here, we compared the effect of human menstrual MSCs (MenSCs) mediated by cell–cell contact, by their total secretome or by secretome-derived extracellular vesicles on neuritic outgrowth in primary neuronal cultures. The contact of MenSCs with cortical neurons inhibited neurite outgrowth while their total secretome enhanced it. The extracellular vesicle fractions showed a distinctive effect: while the exosome-enriched fraction enhanced neurite outgrowth, the microvesicle-enriched fraction displayed an inhibitory effect. When we compared exosome fractions of different human MSC sources, MenSC exosomes showed superior effects on the growth of the longest neurite in cortical neurons and had a comparable effect to BM-SC exosomes on neurite outgrowth in dorsal root ganglia neurons. Thus, the growth-stimulating effects of exosomes derived from MenSCs as well as the opposing effects of both extracellular vesicle fractions provide important information regarding the potential use of MenSCs as therapeutic conveyors in neurodegenerative pathologies.